Pharmacokinetics and outcome of tazobactam/piperacillin in Japanese patients undergoing low-flow continuous renal replacement therapy: dosage considerations - Kohama H; Ide T; Ikawa K; Morikawa N; Nishi S (Dove Medical Press, 2017)
Hanako Kohama,1 Takeshi Ide,1 Kazuro Ikawa,2 Norifumi Morikawa,2 Shinichi Nishi1 1Division of Intensive Care Unit, Hyogo College of Medicine, Nishinomiya, 2Department of Clinical Pharmacotherapy, Hiroshima University, Hiroshima, Japan Background: Tazobactam/piperacillin (TAZ/PIPC), which is often combined with continuous renal replacement therapy (CRRT), induces renal excretion and is thought to have a high component removal rate for blood purification. CRRT procedures vary depending on the country, region, and institution. It is not clear whether the dose of TAZ/PIPC for use in Japan can be determined based on studies conducted in other countries. Therefore, in this study, we examined the suitability of recommended dose in Japan. Methods: The study subjects consisted of 10 patients who received TAZ/PIPC during CRRT in the intensive care unit of Hyogo College of Medicine, Nishinomiya, Japan. We used a one-compartment model to characterize and parameterize the pharmacokinetics of TAZ/PIPC because their blood levels were eliminated monoexponentially. Results: Compared with the data of healthy adults, the half-lives (t1/2) of both PIPC and TAZ were prolonged while their clearance rates decreased. Conclusion: For the continuous hemodiafiltration procedure adopted in Japan, we concluded that the dose and frequency were appropriate because the patients who received PIPC/TAZ 2.25 g twice a day during continuous hemodiafiltration maintained appropriate blood levels of both PIPC and TAZ. Keywords: hemodiafiltration, antibiotics, dosage regimen